How can we design a proper trial for vitamin D treatment of diseases? Facts and numbers - Shuang Zheng; Zhaohua Zhu; Changhai Ding (Wiley, 2023)
Abstract Vitamin D deficiency is a globally common situation and closely related with many chronic diseases. It is a hot topic to examine if vitamin D supplementation is effective for the treatment of diseases, and there have been dozens of clinical trials published in recent years. However, most studies have not proved the extra‐skeletal benefits of vitamin D supplementation on these diseases. Some inherent shortcomings of these trials, such as inclusion with vitamin D‐sufficient and obese participants, low response rate from participants and the insensitive changes in chosen outcomes over a shorter period, may be main reasons why most studies have yet to demonstrate effects of vitamin D supplementation. In this editorial, we aim to discuss the perspectives on how can we design a proper trial for vitamin D treatment of diseases based on the evidence‐based practice framework PICOS (participants, intervention, control, outcomes and study design) in the future. First, right participants should be chosen, which is crucial for the success of vitamin D clinical trials. Participants with vitamin D sufficiency (e.g., baseline 25(OH)D of >50 nmol/L), obesity (e.g., body mass index > 30 kg/m2) and/or high vitamin D response index could be excluded from the trials. Second, intervention with vitamin D in right forms or dosages should be used. Vitamin D3 supplementation with appropriate dosages that keep 25(OH)D levels between 75 and 100 nmol/L is recommended. Third, 'contamination' in the control groups needs to pay attention. To diminish this, it is ideal to include participants less interfered by sun exposure (such as living in places at a high latitude) or with greater compliance (less interference by supplemental vitamin D‐containing nutrients). Fourth, the outcome measures should be sensitive to change to avoid type II error. For outcomes such as bone density, radiographic osteoarthritis and cardiovascular diseases, follow‐up period of 3-5 years may be required to observe the changes. Last, precision clinical trials may be the only way to prove the benefits of vitamin D supplementation.